2008 IEEE Virtual Reality Conference 2008
DOI: 10.1109/vr.2008.4480779
|View full text |Cite
|
Sign up to set email alerts
|

Distance education system for teaching manual skills in endoscopic paranasal sinus surgery using "hypermirror" telecommunication interface

Abstract: We have developed a distance education system for developing skills in endoscopic paranasal sinus surgery, to enable efficient remote training of novices in manual skills such as their standing position and posture, and the insertion angle/depth and holding of surgical instruments. The system uses a precise model of human paranasal sinuses and the "HyperMirror" (HM) telecommunication interface. HM is a virtual mirror allowing clear visualization of differences in manual operation between the trainee and remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…In future extension, for internet-based training and demonstrations, a special network transfer can be developed for transmitting live video with surgical planning and motion data. The education of surgical skills is a common problem in endoscopic surgery 7 that supports the proposed project plan 8 . Personal communications with head physicians in local hospitals confi rm that, inexperienced intervention frequently rearranges the anatomical structures during ENT (Ear Nose and Throat) surgeries that can cause large obstacles in acute cases.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In future extension, for internet-based training and demonstrations, a special network transfer can be developed for transmitting live video with surgical planning and motion data. The education of surgical skills is a common problem in endoscopic surgery 7 that supports the proposed project plan 8 . Personal communications with head physicians in local hospitals confi rm that, inexperienced intervention frequently rearranges the anatomical structures during ENT (Ear Nose and Throat) surgeries that can cause large obstacles in acute cases.…”
Section: Introductionmentioning
confidence: 63%
“…In Endoscopic Paranasal Sinus surgeries 7,8 and other fi elds of endoscopic intervention the real fusion (in time and 3D space) of video sequence and tools' position makes archiving or transmitting information on actual state of surgery possible. This can be used for evaluating problematic results or educating risky interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Arc-shaped forceps are important in pharyngeal cancer surgery, endoscopic sinus surgery [1], and single port surgery [2]. The use of a linear-shaped forceps in pharyngeal cancer surgery requires a patient to bend his or her neck backwards and increases the burden on the patient when compared with the surgery performed by an arc-shaped forceps.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as for the surgical operation, an automatic classification method of four basic surgical operations using a sensing forceps made of a forceps and strain gauges, was proposed in [10]. In [11], it is reported that in surgical operations, a difference arises between skilled surgeon and unskilled surgeon in the following points; the magnitude and direction of the handling force of the object, the manner of having surgical instrument, and surgeon's posture.…”
Section: Introductionmentioning
confidence: 99%